Characteristics of Gabexate Mesilate-Induced Cell Injury in Porcine Aorta Endothelial Cells - Tomoko Aki; Nobuaki Egashira; Mika Hama; Yui Yamauchi; Takahisa Yano; Yoshinori Itoh; Ryozo Oishi (Elsevier, 2008)
Gabexate mesilate (GM), a serine protease inhibitor, often causes severe vascular injury, when injected in high concentration. In the present study, we investigated the mechanisms for the cytotoxicity of GM on porcine aorta endothelial cells (PAECs). GM (0.5 -5.0 mM) decreased cell viability in a dose-dependent manner and caused cell injury, whilst nafamostat mesilate (NM), another serine protease inhibitor, or mesilate itself had no effect on cell viability. zVAD-fmk, a pancaspase inhibitor, or zDEVD-fmk, a caspase-3 inhibitor, did not affect the GM (1.5 mM)-induced decrease of cell viability. Apoptotic cells or DNA fragmentation were also not observed after GM treatment. Moreover, Ca2+chelators, a nitric oxide (NO) synthase inhibitor, antioxidants, and radical scavengers had no effect on the GM-induced cell injury. On the other hand, cellular ATP content was decreased in the GM (2.0 mM)-treated cells. Surprisingly, GM (2.0 mM) immediately increased cellular uptake of propidium iodine. These findings suggest that GM induces necrotic cell death via injury of the cell membrane. Keywords:: gabexate mesilate, nafamostat mesilate, vascular injury, vascular endothelial cell, cytotoxicity